Design and validation of the tactical assessment instrument in football (TAIS) - Barquero-Ruiz, C.; Kirk, D.; Arias-Estero, J. L. (Research Quarterly for Exercise and Sport, 2022)
The focus on tactics has made assessment more difficult due to the lack of knowledge in the topic and the limitations of current tactical assessment instruments. Purpose: To design and validate a tactical assessment instrument in youth football (TAIS) following an exhaustive, ecological and meticulous process and dealing with the limitations found in the literature. Method: The design was divided in two stages related to its development and validation. During the development stage: (a) a preliminary list of criteria was determined through a literature review; (b) the criteria were delimited through an exploratory observation; and (c) the adequacy of the criteria was determined by consulting experts. In the validation stage: (a) content and comprehension validity were obtained by consulting experts and through a systematic game observation; (b) construct validity was obtained by comparing the tactical outcomes from two groups with different skill levels; (c) criterion validity was established by comparing the tactical outcome using Game Performance Assessment Instrument and the present instrument, and (d) the reliability was obtained through inter-rater reliability. Results: The research process showed that the instrument is a valid and reliable tool comprised of 22 criteria to assess tactical outcomes in 8-12 years old youth football. Conclusion: The TAIS presents several advantages in practical terms with respect to assessment. First, it allows assessment of the three tactical levels nested in the unit of observation. Second, it considers all the player roles. Third, results are presented without general indexes. Fourth, it can be used to assess participants from all the institutional contexts. Finally, it includes contextual variables.